Ketamine as a pre-emptive analgesia in patients undergoing caesarean delivery under spinal anesthesia - Humaira Ahmad; Samina Aslam; Sahir Shafiq; Asif Sagheer; Sarwat Bibi (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVES: Lower segment caesarean section (LSCS) leads to moderate to severe pain in the patient. Pain severity is directly proportional to the functional limitations and depression in the postpartum period, making it essential to provide good pain relief after surgery. Maternal wellbeing and better nursing care of newborn requires good postoperative analgesia with minimal side effects. The main objective of the study was to evaluate the analgesic effect of intravenous low-dose ketamine, when administered pre-emptively, in patients undergoing caesarean delivery under spinal anesthesia. METHODOLOGY: Two groups were made, each with 50 full-term pregnant females with a plan of caesarean section under spinal anesthesia. Group-A received spinal anesthesia with bupivacaine 0.5% along with intravenous placebo of 2cc normal saline, whereas group-B received 0.5mg/kg ketamine intravenously after administration of spinal anesthesia but before the start of surgical incision. Pain intensity was monitored using a visual rating pain scale (VRS), till the need for the first analgesic dose postoperatively. RESULTS: Both groups were comparable in terms of age and weight. Analgesia was markedly prolonged, and postoperative pain scores were significantly less in Group-B (ketamine group) as compared to Group-A; with p-value< 0.001, demonstrating analgesic properties of ketamine when administered pre-emptively as an intravenous dose. CONCLUSION: Our study concluded that pre-emptive analgesic dose of ketamine (administered before surgical incision), leads to prolong analgesia in post-operative period in patients who underwent LSCS under spinal anesthesia.